REFLEKSI PEMBERDAYAAN MASYARAKAT DALAM TUGAS GURU PENDIDIKAN AGAMA BUDDHA MELALUI PEMBINA AGAMA (GURU TIDAK TETAP) DI WONOGIRI - Hesti Sadtyadi (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2016)
The purpose of this study was to investigate the implementation of the learning is done by people who become temporary teachers Buddhist education in an effort to meet the needs of the number of teachers who have not been fulfilled, the task execution, knowing temporary teachers in carrying out his duties as a teacher of Buddhist education. This research is a mix research. The result of research, indicate that the implementation of the learning undertaken by temporary teachers of Buddhist education in an effort to meet the needs of the teacher is the optimal number, and All teachers have done their job well, with components that should receive special attention is in the use of media and or learning strategies. If the evaluation is done thoroughly in the process of learning plans then seen the incomplete learning plan performed as in the case of making worksheets, clarity sources, lack of subject content validity, and if it is seen only in the process of learning plans in particular RPP (Learning Implementation Plan), specifically on learning plan in the classroom, regardless of other aspects) resulting deficiencies in the methods and learning strategies are used.